Organizational culture and constructions of the customer - Alvesson, Mats, 1956- ([London] : SAGE, 2016)
The case is based on an ethnographic study of the editorial wing of a Swedish evening newspaper. It examines the newspaper's organizational culture and its influence on marketing and the construction of the customer.
Originally Published in: Alvesson, M. (2012). Organizational Culture and Constructions of the Customer: A Case Study. In Understanding organizational culture (2nd ed., pp. 94-97). London: SAGE Publications Ltd. ISBN: 9780857025586.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Consumer behavior -- Case studies; Corporate culture -- Case studies; Mass media -- Influence -- Case studies